2021
DOI: 10.3390/ijerph18115862
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Wellbeing during the COVID-19 Pandemic: The Influence of Personality Traits in the Italian Population

Abstract: Coronavirus disease 19 (COVID-19) has had a strong psychological impact on the Italian population. Italy was heavily affected by the virus before other countries in Europe, experiencing the highest number of deaths. Unknown symptoms in the early stages of the pandemic and the absence of clear transmission links affected people’s wellbeing. Individual personality differences played a key role in perceived psychological wellbeing during the pandemic. The present exploratory study sought to evaluate the impact of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 49 publications
0
15
0
1
Order By: Relevance
“…Combining findings from the present study with Rossi et al. (2021) , it is possible that upon the onset of COVID-19 many people experienced helplessness and vulnerability within the broader population, as they were unsure of ways to keep themselves and loved ones safe during the pandemic.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Combining findings from the present study with Rossi et al. (2021) , it is possible that upon the onset of COVID-19 many people experienced helplessness and vulnerability within the broader population, as they were unsure of ways to keep themselves and loved ones safe during the pandemic.…”
Section: Discussionmentioning
confidence: 72%
“…Additionally, in this project we sought to estimate the relatively increased prevalence rates of psychopathology during the COVID-19 era; however, we did not investigate the mechanisms by which these increased rates came about. Recent literature within an Italian sample points to vulnerability and helplessness as contributors to the development and exacerbation of psychopathology ( Rossi et al., 2021 ). It is possible that these factors contribute psychopathology to other populations.…”
Section: Discussionmentioning
confidence: 99%
“…The results provided by the ANOVAs showed very low levels of psychological well-being in women. This first result is in line with other studies that have reported a significantly higher level of distress in women (Lathabhavan, 2021 ; Rossi et al ., 2021 ). Furthermore, a recent meta-analysis conducted by Wang et al .…”
Section: Discussionmentioning
confidence: 99%
“…Menurut Ryff & Keyes, (1995) Model teoritis kesejahteraan psikologis yang mencakup 6 dimensi kesehatan yang berbeda (Otonomi, Penguasaan Lingkungan, Pertumbuhan Pribadi, Hubungan Positif Dengan Orang Lain, Tujuan Hidup, Penerimaan Diri) Psychological wellbeing adalah sebagai kemampuan individu untuk menerima diri apa adanya, membentuk hubungan yang hangat dengan orang lain, memiliki kemandirian dalam menghadapi lingkungan sosial, mengontrol lingkungan eksternal, menetapkan tujuan hidupnya, dan merealisasikan potensi dirinya secara kontinu (Rossi, Bonanomi, & Oasi, 2021).…”
Section: Kesejahteraan Atlet (Athlete Wellbeing)unclassified